KUALITAS PELAYANAN PUBLIK PADA PT. JASA RAHARJA (PERSERO) KOTA PEKANBARU - Yanti, Melda Ria; Rusli SD, Zaili (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The increase of traffic users become the reason of increasing number of traffic incident victims. Resulting on the increase of claims for traffic accident health insurance compensation filing to Jasa Raharja insurance company. The problems that become the main concern is not every people/victims/victim heirs of insurance from traffic accident who filed the claim got what they deserve. Government from law number 33 and 34 year 1964 about Traffic Accident Funds has set up state company that engaged in insurance which is PT Jasa Raharja expected to handle these problems. PT Jasa Raharja’s duty and resposibillity is to give compesation to people who had an accident according to law number 33 and 34 year 1964, by collecting and managing dues and compulsory contributions hencefort be given to victims or heirs of insurance through compensation.The purpose of this research is to know the quality of public service on PT Jasa Raharja of Pekanbaru. The theory used in this research is the quality public service theory. The method of this research is qualitative descriptive, which in gathering data researcher used interview method, and library research. The results of this research indicate that the quality of public service in PT Jasa Raharja of Pekanbaru still not maximal and in need of socialization so that people would understand the way to get insurance from the government.keywords: quality of service, public services, services in insurance